2002
DOI: 10.1093/alcalc/37.2.179
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Effects of Ethanol, Acetaldehyde and Fatty Acid Ethyl Esters on Human Erythrocytes

Abstract: In vitro experiments were performed to determine if ethanol was metabolized by human erythrocytes and to investigate if ethanol or its metabolites, acetaldehyde and fatty acid ethyl esters, affected erythrocyte morphology and stability. No detectable metabolism of ethanol was found in erythrocytes, although ethanol itself caused an elevated rate of spontaneous haemolysis in erythrocyte preparations. Physiologically attainable levels of ethanol were found to stabilize erythrocytes against haemolysis induced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 39 publications
1
12
0
1
Order By: Relevance
“…Further investigation is necessary to determine if the observed FAEE changes in RBCs are related to the RBC membrane disorders associated with chronic ethanol ingestion. Recently in an in vitro study, Tyulina et al showed that FAEEs cause elevated RBC hemolysis and significant elevations in phosphatidylserine externalization to the outer leaflet of the membrane bilayer (41). In this study, the observed changes were not due to ethanol or acetaldehyde, a product of oxidative ethanol metabolism.…”
Section: Resultssupporting
confidence: 50%
See 1 more Smart Citation
“…Further investigation is necessary to determine if the observed FAEE changes in RBCs are related to the RBC membrane disorders associated with chronic ethanol ingestion. Recently in an in vitro study, Tyulina et al showed that FAEEs cause elevated RBC hemolysis and significant elevations in phosphatidylserine externalization to the outer leaflet of the membrane bilayer (41). In this study, the observed changes were not due to ethanol or acetaldehyde, a product of oxidative ethanol metabolism.…”
Section: Resultssupporting
confidence: 50%
“…In this study, the observed changes were not due to ethanol or acetaldehyde, a product of oxidative ethanol metabolism. They also revealed that the effects of FAEE on RBC instability and structure were more pronounced when albumin was absent (41). This finding may explain why altered RBC morphology occurs with alcoholic liver disease, given that injured livers often synthesize decreased amounts of albumin.…”
Section: Resultsmentioning
confidence: 87%
“…Optical density was monitored at 630 nm every 0.25 s after the initiation of hypoosmotic stress to assess hemolysis. A detailed description of this method may be found elsewhere (48). Cellular fragility was determined by monitoring shear stress-induced hemolysis.…”
Section: Methodsmentioning
confidence: 99%
“…Although FAEEs have been shown to induce ROS generation in hepatocytes [44] and blood cells [45], no such data were available with respect to intestinal cells. In this study, exposure to EO and EP dose-dependently increased ROS generation in Caco-2 spheroids.…”
Section: Discussionmentioning
confidence: 99%